2014
DOI: 10.7326/m14-0933
|View full text |Cite
|
Sign up to set email alerts
|

Financial Conflicts of Interest and Conclusions About Neuraminidase Inhibitors for Influenza

Abstract: Australian National Health and Medical Research Council.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
45
1
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(51 citation statements)
references
References 60 publications
1
45
1
4
Order By: Relevance
“…These studies have often examined financial and non-financial competing interests [10, 11, 15]. In each case, the analyses demonstrated that authors of systematic reviews may introduce biases in the design and reporting of systematic review to produce conclusions that are aligned with their interests.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies have often examined financial and non-financial competing interests [10, 11, 15]. In each case, the analyses demonstrated that authors of systematic reviews may introduce biases in the design and reporting of systematic review to produce conclusions that are aligned with their interests.…”
Section: Discussionmentioning
confidence: 99%
“…Analyses in other domains have found that financial conflicts of interest can be associated with differences in the interpretation of the results when drawing conclusions and making recommendations [1012]. Specific to mammography, an analysis of mostly primary studies showed that authors who worked directly in mammography screening were more likely to downplay or reject over-diagnosis than other authors [13].…”
Section: Introductionmentioning
confidence: 99%
“…хорошо известно, что многие ис-следования с отрицательным результатом часто не публикуются. Систематические обзоры эффективности ингибиторов нейраминидазы продемонстрировали эффективность в 88% в исследованиях с конфликтом интересов, и только 17% -без такового [19].…”
Section: мета-анализы исследований и систематические обзорыunclassified
“…Bolstered by this ease of electronic literature searches, however, although publications of systematic reviews and meta-analyses (SRMAs) have increased exponentially over the last decade, there has not been comparable improvement in methodological rigor or reporting standards [2]. Meanwhile, studies linking favorable meta-analysis outcomes with financial conflicts of interest of authors have highlighted the susceptibility of SRMAs to manipulation [35]. Amidst these findings, while some have questioned the position of SRMAs as the highest level of evidence [6], others have called for ensuring greater objectivity and reproducibility in producing them [7].…”
Section: Introductionmentioning
confidence: 99%